Nature conservation in Europe approaches and lessons - Tucker, Graham (Cambridge University Press, 2023)
European ecosystems and species remain under pressure from intensive agriculture and forestry, fishing, pollution, urban sprawl, invasive species and climate change. This book provides a detailed description and critical analysis of nature conservation responses, achievements and failures, motivated by the concerning state of nature and missed biodiversity targets. It summarises Europe's nature and the impact of human activities, and then gives an overview of relevant international biodiversity treaties and the EU nature conservation policy and legislative framework. The core of the book comprises chapters written by national experts, which cover the UK and twenty-five EU Member States, providing comparative case studies from which valuable lessons are drawn. Covering wide-ranging topics such as biodiversity pressures, legislation and governance, biodiversity strategies, species protection, protected areas, habitat management, and funding, this book is of interest to a wide audience, including academics and professionals involved in nature conservation and related environmental fields